INVESTIGATING THE IMPACT OF WORK DISCIPLINE, WORK ABILITY, AND WORK SUPERVISION ON EMPLOYEE WORK EFFECTIVENESS IN ROAD MAINTENANCE AND IMPROVEMENT WITHIN THE PUBLIC WORKS SERVICE AND SPATIAL PLANNING OF CIREBON REGENCY - Mahfud; Wawat Hermawati; Tadi Aryadi (PT. Berkah Digital Teknologi, 2024)
Purpose: To investigate the impact of work discipline, work ability, and work supervision on employee work effectiveness in the field of road maintenance and improvement at the Public Works Service and Spatial Planning of Cirebon Regency. Research Methodology: Quantitative method, descriptive analysis, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, hypothesis testing with partial regression test (t test). Results: Work discipline, work ability, and work supervision positively influence employee work effectiveness. Limitations: Limited sample size of 60 employee respondents. Contribution: Provides insights for enhancing work effectiveness in road maintenance and improvement services in public works and spatial planning contexts.